Adaptive feedback in computer-based learning environments: a review. (October 2017) - Bimba, Andrew Thomas; Idris, Norisma; Al-Hunaiyyan, Ahmed; Mahmud, Rohana Binti; Shuib, Nor Liyana Bt Mohd
Adaptive support within a learning environment is useful because most learners have different personal characteristics such as prior knowledge, learning progress, and learning preferences. This study reviews various implementation of adaptive feedback, based on the four adaptation characteristics: means, target, goal, and strategy. This review focuses on 20 different implementations of feedback in a computer-based learning environment, ranging from multimedia web-based intelligent tutoring systems, dialog-based intelligent tutoring systems, web-based intelligent e-learning systems, adaptive hypermedia systems, and adaptive learning environment. The main objective of the review is to compare computer-based learning environments according to their implementation of feedback and to identify open research questions in adaptive feedback implementations. The review resulted in categorizing these feedback implementations based on the students' information used for providing feedback, the aspect of the domain or pedagogical knowledge that is adapted to provide feedback based on the students' characteristics, the pedagogical reason for providing feedback, and the steps taken to provide feedback with or without students' participation. Other information such as the common adaptive feedback means, goals, and implementation techniques are identified. This review reveals a distinct relationship between the characteristics of feedback, features of adaptive feedback, and computer-based learning models. Other information such as the common adaptive feedback means, goals, implementation techniques, and open research questions are identified.